Changes in Brain Neuroimmunology Following Injury and Disease - Tabet, Anthony; Apra, Caroline; Stranahan, Alexis M.; Anikeeva, Polina (Frontiers in Integrative Neuroscience, 2022)
The nervous and immune systems are intimately related in the brain and in the periphery, where changes to one affect the other and vice-versa. Immune cells are responsible for sculpting and pruning neuronal synapses, and play key roles in neuro-development and neurological disease pathology. The immune composition of the brain is tightly regulated from the periphery through the blood-brain barrier (BBB), whose maintenance is driven to a significant extent by extracellular matrix (ECM) components. After a brain insult, the BBB can become disrupted and the composition of the ECM can change. These changes, and resulting immune infiltration, can have detrimental effects on neurophysiology and are the hallmarks of several diseases. In this review, we discuss some processes that may occur after insult, and potential consequences to brain neuroimmunology and disease progression. We then highlight future research directions and opportunities for further tool development to probe the neuron-immune interface.